2013
DOI: 10.1371/journal.pone.0082326
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation Is Minimally Influenced by the Superior Cervical Ganglion in Two- Week-Old Lambs, and Absent in Preterm Lambs Immediately Following Delivery

Abstract: Cerebral vessels in the premature newborn brain are well supplied with adrenergic nerves, stemming from the superior cervical ganglia (SCG), but their role in regulation of blood flow remains uncertain. To test this function twelve premature or two-week-old lambs were instrumented with laser Doppler flow probes in the parietal cortices to measure changes in blood flow during changes in systemic blood pressure and electrical stimulation of the SCG. In lambs delivered prematurely at ∼129 days gestation cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Importantly, we have shown that the lamb brain at this gestational age is still susceptible to brain inflammation and white matter damage from ventilation [5,6,18] . Further, cerebral autoregulation has been shown to be impaired in preterm ventilated lambs of this age [51] . We believe that early EPO administration is necessary to target pathways of VIBI and prevent injury manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have shown that the lamb brain at this gestational age is still susceptible to brain inflammation and white matter damage from ventilation [5,6,18] . Further, cerebral autoregulation has been shown to be impaired in preterm ventilated lambs of this age [51] . We believe that early EPO administration is necessary to target pathways of VIBI and prevent injury manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha1ARs are the major regulator of norepinephrine-mediated vascular regulation 28 , 38 , 57 . With developmental maturation, the adrenergic system undergoes significant changes, which play an important role in CBF regulation and cellular/vascular growth including angiogenesis 21 , 22 , 26 , 38 , 57 , 59 61 . In our previous studies, we have demonstrated that the premature fetus lacks the sympathetic system-mediated regulation of CBF 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that the sympathetic system has a little biological significance in cerebral vasculature 24 , 25 . In contrast, evidence, particularly in a developing organism, supports a dynamic role in cerebrovascular autoregulation in response to changes in blood pressure 26 29 , and in the maintenance of cerebrovascular tone 30 . An important barrier towards the study of the role of norepinephrine was its inability to cross the blood-brain barrier 16 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations